[PP.20.08] THE INFLUENCE OF SLOW BREATHING TRAINING ON QUALITY OF LIFE IN PATIENTS WITH CHRONIC HEART FAILURE. (September 2016) - Drozdz, T.; Klocek, M.; Debicka-Dabrowska, D.; Styczkiewicz, K.; Malfatto, G.; Bednarek, A.; Olszanecka, A.; Kielbasa, G.; Bilo, G.; Czarnecka, D.; Parati, G.; Kawecka-Jaszcz, K.
Abstract : Objective: Slow breathing training (SBT) was shown to have favorable acute effects in chronic heart failure (CHF) patients. Aim of this study was to test the influence of SBT on quality of life (QoL) in these patients. Design and method: The study was a cross-over open trial where patients, in random order, underwent a 10–12 week period of SBT with RESPeRATE device (InterCure Ltd., Lod, Israel) and a 10–12 week follow-up under usual care. Patients during SBT were asked to perform each day two separate 15-min sessions of device-guided SBT at a breathing frequency of 6 breaths per minute. In all patients QoL was assessed with Minnesota Living with Heart Failure questionnaire performed at baseline and after each study phase. QoL was assessed both globally and separately for physical, socio-economical and emotional aspects. Results: 74 patients completed the study. with the following baseline characteristics: age 62.9 ± 11.9 years, 59 M/15F, 52 with ischemic CHF, NYHA Class I:7 Class II:51, Class III:16, left ventricular ejection fraction 30.4 ± 8.1 %, hypertension: 47, history of stroke: 5, diabetes: 28. In subjects who completed SBT phase, total and physical QoL scores before and after SBT were 49.0 (41.0–56.0) vs 46.0 (37.5–52.0), p < 0.001, and 22.0 (19.0–25.0) vs. 20.0 (16.0–23.0), p = 0.006, respectively. There were no significant differences in socio-economical [21.5 (17.0–24.0) vs. 21.0 (16.0–23.0); p = 0.200] and emotional [5.0 (3.0–7.0) vs 4.0 (3.0–6.0); p = 0.718] aspects of QoL. Conclusions: Our data indicate that SBT is safe in CHF subjects, and may improve their quality of life, mostly due to an improvement in exercise capacity. These results are in line with our previous finding of increased 6 minute walk distance in this sample, and further support SBT as a novel and useful component of cardiorespiratory rehabilitation programs in CHF.